2005
DOI: 10.1159/000083928
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Study on Cu/Zn Superoxide Dismutase Induction by Hemodialysis Treatment

Abstract: Background/Aims: There is little or no controversy about the increased oxidative stress of hemodialysis (HD) patients. Several reports show that the activity of superoxide dismutase (SOD), one of the major endogenous antioxidant enzymes, in plasma is elevated among HD patients. It is still unclear, however, whether this elevation is due to the promotion of SOD production or a decrease in renal excretion of SOD. This study was designed to investigate the cause of the SOD activation in HD patients, and we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…Noteworthy enough, we found a 2.0-fold increase of Cu/Zn-SOD mRNA in leukocytes in hemodialysis patients as compared with the same in healthy controls. Also we found 1.7-fold increase of Cu/Zn-SOD mRNA in hemodialysis patients as compared with the same in non-dialyzed CRF patients [14]. We speculate this finding is probably due to the direct contact of leukocytes with dialyzer membrane.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Noteworthy enough, we found a 2.0-fold increase of Cu/Zn-SOD mRNA in leukocytes in hemodialysis patients as compared with the same in healthy controls. Also we found 1.7-fold increase of Cu/Zn-SOD mRNA in hemodialysis patients as compared with the same in non-dialyzed CRF patients [14]. We speculate this finding is probably due to the direct contact of leukocytes with dialyzer membrane.…”
Section: Introductionmentioning
confidence: 74%
“…VE-PO resulted in a progressive decrease in Cu/Zn-SOD content (from 3.0 ± 1.6 to 0.6 ± 0.6; p < 0.01), which reached the level of non-dialyzed CRF patients by 6 months [14]. Similarly, a concomitant progressive decrease was observed in VE-BMD (from 3.6 ± 1.6 to 0.7 ± 0.4; p < 0.01), suggesting an associated diminution in oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Akiyama et al reported that Cu/Zn-SOD mRNA levels were also high in the white blood cells of these patients, thus leading to increased Cu/Zn-SOD production [12]. On the other hand, Futenma et al examined Cu/Zn-SOD isomers using gel column chromatography and revealed that despite a decrease in tetramers or octamers of Cu/Zn-SOD, there was a marked increase in Cu/Zn-SOD levels in hemodialysis patients owing to an increase in monomers of Cu/ Zn-SOD that are immunologically active but enzymatically inactive [26].…”
Section: High Levels Of Serum Cu/zn-sod In Hemodialysis Patientsmentioning
confidence: 94%
“…We previously reported increased Cu / Zn-superoxide dismutase SOD in the blood and upregulated Cu / Zn-SOD mRNA in the leukocytes of hemodialysis patients, as well as a correlation between leukocyte membrane lipid peroxidation and expression of Cu / Zn-SOD mRNA in hemodialysis patients ; this causes oxidative stress which may also occur due to blood cell contact with the dialysis membrane 7,8 . Dialysis-associated oxidative stress is in response to depletion of the intracellular ATP supply, shifting to other intracellular glucose metabolic pathways, such as the polyol pathway from the glycolytic system, hexosamine pathway, pentose phosphate pathway, and protein kinase C pathway 12,13 , however many aspects of this shift are not well defined.…”
Section: Introductionmentioning
confidence: 99%